Studi Fisika Tanah pada Budi Daya Tembakau (Nicotiana tabacum L) di Berbagai Kemiringan Lahan - Adrinal Adrinal; Gusmini Gusmini; Elsa Lolita Putri; Ghina Nadifa (Institut Pertanian Bogor, 2024)
The percentage of slope classes on a land has an impact on changes in soil physics. The purpose of this study is to evaluate the physical properties of soil planted with tobacco on various slopes in Kenagarian Situjuah Batua, Situjuah Limo Nagari District, Lima Puluh Kota Regency. The method used in this study was a survey; samples were taken purposively based on slope classes at slopes 8-15%, 15–25%, and 25–45% at depths of 0–20 cm and 20–40 cm. From each slope 3 repetitions were taken. The results showed that there were changes in soil physics properties in each slope class with the dominant texture of sandy clay loam. Organic matter was classified as high to low (18.77–3.63%), low soil buld density (0.66–0.34 g/cm3), and total pore space was classified as high (75.27–86.87%). The permeability of the soil was classified as very fast to somewhat slow (34.88–0.78 cm/h), and the aggregate stability index was somewhat steady to less steady (60.89–45.98%). It is recommended that tobacco farmers to make terrracing and cut the length of the slope so that it does not lose organic matter. Keywords: soil physical properties, slope level, tobacco plantation